ASC annual report 1998 - 1999 (Annual report Australian Sports Commission, 1999)
It was a year in which we made final adjustments to the Olympic Athlete Program and the Sports Assistance Scheme. The Board took deliberate steps to ensure that our funding is now performance based. In respect of the OAP, it is directed toward the athletes and sports that are likely to be our best performers in the Sydney 2000 Olympics and Paralympics, while funding to sporting organisations is based on achieving agreed outcomes within each sport`s management plan. In a sense the hard work is now behind us. Training, competition, coaching, sport science and support programs are now fully in place — the rest is up to the individual and the prevailing conditions on the day. Australian sport, post 2000, needs to be more professional, outward-looking, client focused and self-sustaining. The Board spent a great deal of time during the year independently researching our past and future responsibilities and commitments. We have looked beyond the immediate future and determined our role in a post-Olympic era. Management undertook an environmental scan to evaluate the services and funding provided to elite athletes nationally and to identify areas of duplication between programs at the Australian Institute of Sport (AIS) and state institutes and academies.